PENGARUH KEPUASAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ASTRA MULTI FINANCE (AMF) SPEKTRA SEMARANG - Nanda Panji M. Eko Restu H, 09.05.51.0057 (Students Journal of Economic and Management, 2014)
This study aims to examine and analyze the effect of job satisfaction, motivation and discipline of employees working on the performance of PT. AMF SPEKTRA Semarang. This study was conducted using census and executed on 65 AMF SPEKTRA PT Semarang. Testing data used in this study include testing the validity of the product moment, with a Cronbach alpha reliability test, multiple linear regression analysis, t-test to test and prove the research hypothesis. Data collected was tested for validity with product moment analysis method and tested reliability with coefficient alpha (Cronbach alpha), where the result is expressed throughout the data valid and reliable. The results of the analysis and discussion show that: (1). Job satisfaction has a positive effect on employee performance. higher job satisfaction, higher employee performance as well; (2). motivation has a positive effect on employee performance, higher employee motivation, employee performance is also higher; (3). Labor discipline positive effect on employee performance, higher employee discipline, employee performance is also higher. Keywords: Job Satisfaction, Motivation, Work Discipline, Employee Performance